2015
DOI: 10.1093/bib/bbv039
|View full text |Cite
|
Sign up to set email alerts
|

Systems biological approaches to the cardiac signaling network

Abstract: Recent systems biological studies of cardiac systems have greatly advanced our understanding of cardiac physiology with a particular focus on the excitation-contraction coupling. With these advancements, there is a growing interest in systems analysis of the cardiac signaling network because its dynamical property is closely associated with cardiac diseases. In this article, we review recent attempts at computational modeling of the cardiac signaling network and provide a system-level perspective on the analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 107 publications
0
10
0
Order By: Relevance
“…In contrast to the larger number of models of short-term (milliseconds to minutes) cardiac myocyte physiology, fewer models have examined the molecular networks that control longer-term gene expression and remodelling (hours to days) 269,280 . Tavi and colleagues used a model of calcium-calmodulin-calcineurin kinetics to show that calcineurin might act as a frequency-sensitive integrator of cytosolic calcium signals 281,282 , which correlates with experimental measurements of NFAT activity, mRNA expression 281 and myocyte hypertrophy 283 .…”
Section: Systems Models Of Mechanosignallingmentioning
confidence: 99%
“…In contrast to the larger number of models of short-term (milliseconds to minutes) cardiac myocyte physiology, fewer models have examined the molecular networks that control longer-term gene expression and remodelling (hours to days) 269,280 . Tavi and colleagues used a model of calcium-calmodulin-calcineurin kinetics to show that calcineurin might act as a frequency-sensitive integrator of cytosolic calcium signals 281,282 , which correlates with experimental measurements of NFAT activity, mRNA expression 281 and myocyte hypertrophy 283 .…”
Section: Systems Models Of Mechanosignallingmentioning
confidence: 99%
“…We have included much “crosstalk” between various signaling cascades, but have not yet incorporated feedback loops or micro-RNA regulation. Dynamic activation of input signals and feedback loops are likely necessary to fully capture the complexities of in vivo cardiac hypertrophy and its progression to heart failure [30]. Despite these limitations, we found this network model predicts in vivo responses of cellular and organ hypertrophy and cardiac gene expression with 78% concordance.…”
Section: Discussionmentioning
confidence: 92%
“…While additional complexity in the signaling model may help to discriminate subtleties in the timing and gene expression changes and species specificity of the hypertrophy response, development of multi-scale models may be required to predict clinical phenotypes such as eccentric vs. concentric and physiologic vs. pathologic hypertrophy. Systems biology approaches to describing organ and organism level responses related to circulatory stressors will require integration of multiple phenotypic responses, such as hypertrophy signaling, apoptosis, fibrosis, and contractility, across varying time-scales using complex multi-scale modeling [30]. The ability of the hypertrophy signaling network model to predict in vivo hypertrophy of transgenic mouse models indicates that this computational model will be a strong basis for understanding multi-scale relationships between molecular regulation and organ level remodeling.…”
Section: Discussionmentioning
confidence: 99%
“…But, due to the substantial complexity in calcium signaling in excitable cells such as cardiomyocytes, conventional experimental approaches have limitations in understanding the CaN/NFAT signaling in these cells (Goonasekera and Molkentin 2012). Nowadays, using systems biological approaches has been covered these shortcomings to an acceptable extent and provide an apparatus to investigate complex signaling networks such as CaN/NFAT signaling (Kang et al 2016). In this regard, Fisher et al (2006) simulated the NFAT activation in T lymphocytes (T cells) and showed that NFAT activity is not sensitive to the low frequencies of Ca 2+ oscillations.…”
Section: Introductionmentioning
confidence: 99%